Up-regulation of placental leptin by human chorionic gonadotropin - Maymo, Julieta Lorena (2009)
Leptin, the 16,000 molecular weight protein product of the obese gene, was originally considered as an adipocyte-derived signaling molecule for the central control of metabolism. However, leptin has been suggested to be involved in other functions during pregnancy, particularly in placenta, in which it was found to be expressed. In the present work, we have found that recombinant human chorionic gonadotropin (hCG) added to BeWo choriocarcinoma cell line showed a stimulatory effect on endogenous leptin expression, when analyzed by Western blot. This effect was time and dose dependent. Maximal effect was achieved at hCG 100 IU/ml. Moreover, hCG treatment enhanced leptin promoter activity up to 12.9 times, evaluated by transient transfection with a plasmid construction containing different promoter regions and the reporter gene luciferase. This effect was dose dependent and evidenced with all the promoter regions analyzed, regardless of length. Similar results were obtained with placental explants, thus indicating physiological relevance. Because hCG signal transduction usually involves cAMP signaling, this pathway was analyzed. Contrarily, we found that dibutyryl cAMP counteracted hCG effect on leptin expression. Furthermore, cotransfection with the catalytic subunit of PKA and/or the transcription factor cAMP response element binding protein repressed leptin expression. Thereafter we determined that hCG effect could be partially blocked by pharmacologic inhibition of MAPK pathway with 50 microM PD98059 but not by the inhibition of the phosphatidylinositol 3-kinase pathway with 0.1 microm wortmannin. Moreover, hCG treatment promoted MAPK kinase and ERK1/ERK2 phosphorylation in placental cells. Finally, cotransfection with a dominant-negative mutant of MAPK blocked the hCG-mediated activation of leptin expression. In conclusion, we provide some evidence suggesting that hCG induces leptin expression in trophoblastic cells probably involving the MAPK signal transduction pathway.